만성 편마비 환자의 발목에 적용한 능동운동을 동반한 관절가동술이 하지근력과 보행의 시공간적 변수에 미치는 영향 - 안창만; Chang Man An; 원종임; Jong Im Won (Han'guk Chŏnmun Mulli Ch'iryo Hakhoe chi = Journal of the Korean Academy of University Trained Physical Therapists, 2012)
The purpose of this study was to determine the effect of ankle joint mobilization with movement (MWM) on the range of motion (ROM) in the ankle, on the muscle strength of lower extremities, and on spatiotemporal gait parameters in chronic hemiplegic patients. Fifteen subjects with chronic stroke were divided into two groups: an experimental group (8 subjects) and a control group (7 subjects). Both groups attended two or three sessions of physical therapy each week. The experimental group also attended additional MWM training sessions three times a week for five weeks. For both groups, the ROM of the ankle, the muscle strength of the lower extremities, and the spatiotemporal gait parameters in paretic limbs were evaluated before and after the training period. The results showed that the experimental group experienced more significant increases than did the control group in terms of passive (6.10％) and active (21.96％) ROM of the ankle, gait velocity (12.96％), and peak torque, of the knee flexor (81.39％), the knee extensor (24.88％), and the ankle plantar flexor (41.75％)(p<.05). These results suggest that MWM training in patients with chronic stroke may be beneficial in increasing ROM in the ankle, muscle strength in the lower extremities, and gait speed.